The Effect of Warm Compress with Lavender Aromatherapy on Reducing Dysmenorrhea Pain in Adolescent Girls - Vika Tri Zelharsandy; Marchatus Soleha; Wika Sepiwiryanti; Rini Anggeriani (Indonesian Journal of Global Health Research, 2025)
Dysmenorrhea is a menstrual disorder that is felt in the form of pain or abdominal cramps. Dysmenorrhea can be reduced using pharmacological and non-pharmacological therapy. An example of non-conventional therapy in overcoming dysmenorrhea is by using warm compresses with lavender aromatherapy which provides a double effect, namely warm compresses and lavender aromatherapy which can reduce the level of dysmenorrhea. The purpose of this study was the effect of warm compresses with lavender aromatherapy on reducing dysmenorrhea pain in adolescent girls in the Sumber Deras Village Health Center Work Area. The research method used was experimental research with the One Group Pre-Test and Post-test Design approach. Sampling was carried out using purposive sampling technique with a total of 36 adolescent female respondents who experienced dysmenorrhea. The data analysis used was the Wilcoxon Test. The results of univariate analysis showed that from 36 respondents, most of the female adolescents before being given warm compresses and lavender aromatherapy experienced moderate pain as many as 29 people (80.6%), all female adolescents after being given warm compresses and lavender aromatherapy had no pain as many as 36 people (100%), there was an effect of warm compresses with lavender aromatherapy on reducing dysmenorrhea pain in female adolescents in the Working Area of the Sumber Deras Village Health Center with a p value = 0.000 <α = 0.05. It is expected that female adolescents can overcome dysmenorrhea pain with non-pharmacological efforts of warm compresses with lavender aromatherapy.